Laminin receptors on Candida albicans germ tubes. - Bouchara, J P (1990)
Recent evidence for the role of laminin in cell adhesion and in the pathogenesis of several bacterial infections has led us to investigate the existence of receptors for this extracellular matrix component in Candida albicans. At first, immunofluorescence demonstrated the presence of laminin-binding sites at the surface of germ tubes. Electron microscopy confirmed this result and permitted precise localization of the binding sites on the outermost fibrillar layer of the germ tube cell wall. By using 125I-radiolabeled laminin, the binding was shown to be saturable and specific, hence demonstrating characteristics of true receptors. Analysis of the data by the Scatchard equation indicated that there were about 8,000 binding sites per cell, with a dissociation constant (Kd) of 1.3 x 10(-9) M. Binding was inhibited by prior heating or trypsinization of cells. Furthermore, of the different proteins and carbohydrates tested in competition experiments, only fibrinogen greatly reduced the laminin binding. Finally, dithiothreitol and iodoacetamide treatment of germ tubes allowed us to identify the laminin receptors through analysis of this extract by sodium dodecyl sulfate-polyacrylamide gel electrophoresis and Western immunoblotting. Two components, of 68 kilodaltons and a doublet of 60 and 62 kilodaltons, were detected. Thus, C. albicans possesses germ tube-specific surface receptors for laminin which could mediate its attachment to basement membranes and so contribute to the establishment of candidiasis.